2012
DOI: 10.1134/s1027451012050072
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the elemental composition of sapropel from Lake Kirek (West Siberia) by SR XFA technique

Abstract: The synchrotron radiation X ray fluorescence analysis (SRXFA) technique was applied for scan ning two sapropel cores: 6.2 m (coordinates of boring 56°11Ј93Љ N, 84°23Ј22Љ E) and 3.6 m (56°10Ј93Љ N, 84°22Ј94Љ E), obtained at a depth of 5 and 7 m, respectively, in Lake Kirek (southern part of Tomsk oblast, West Siberia). Based on variations in the content of eight chemical elements in stratified core horizons, the geochemical types of the sapropels and their prevalence were established. In the sediment of the 6.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The increase in the evolving CO 2 in the present work showed that the yeast performance (i.e., metabolic activity) was high and could be molded to increase yield. However, HS (HA and humin), or other elements present in UDHSS [38,39], do not seem to have significant effects on the released CO 2 .…”
Section: Variation Of Carbon Dioxide During Fermentationmentioning
confidence: 99%
“…The increase in the evolving CO 2 in the present work showed that the yeast performance (i.e., metabolic activity) was high and could be molded to increase yield. However, HS (HA and humin), or other elements present in UDHSS [38,39], do not seem to have significant effects on the released CO 2 .…”
Section: Variation Of Carbon Dioxide During Fermentationmentioning
confidence: 99%